Genetics : - Brooker, Robert J. (McGraw-Hill / Irwin, 2005)
Genetics: Analysis and Principles emphasizes the scientific method to give students the insight needed to develop scientific reasoning skills. Thirty-six text-integrated experiments in transmission and molecular genetics follow the five-step scientific method as they show students the "how" (experimental procedures) and "why" (the underlying scientific principles) behind important experiments that created the current body of genetics knowledge.